A lízing történeti fejlődése - Varga, Nelli (Debreceni Jogi Műhely, 2009)
The mostly economy-inspired legal institution of lease is a relatively new “multidimensional” formation in our law of obligations. Its evolution and development were mostly influenced by economic factors and motivations, which even today determine the intensity of its development. The historical and present day evolution of lease is closely intertwined with the current environment of tax law, accounting and the economy: favourable legal regulation or economic media may result in increased volumes of lease, while an unfavourable legislatorial decision or economic atmosphere may bring setbacks. Historical development in the event of lease is inseparably intertwined with considerations of economics.The essay intends to provide an overview of the historical development of lease. We would like to present the development stages of lease in Hungary and on an international level. Outlining the historical development of lease, our purpose is to represent business, tax law and accounting impetuses that had a definitive role in the development and propagation of lease.